Modern radar system analysis software & uers manual version 2.0 - Barton, David Knox, 1927-; Barton, William F. (1993)
Provides accurate calculations of the maximum detection range of a pulsed radar under a variety of environmental conditions involving thermal noise, jamming, and all types of clutter.
Title from disk label.
System requirements: IBM PC or compatible; at least 512K; DOS 3.0 or higher; hard disk; monochrome or color monitor; adapter card (EGA, VGA, Hercules) and printer (optional).
LC has 2 copies.
Keywords: Radar -- Software. -- EL, MS COMM